IR a Qualitative Comparative Analysis on Internal Conditions leading to high disclosure levels in the case of European State-Owned Enterprises: Array - Gianluca, Zanellato (The Journal of Accounting and Management, 2022)
The present paper aims to investigate the disclosure practices in State-Owned European organizations issuing an Integrated Reporting. Under the legitimacy theory, the paper investigates a total of 24 organizations from 2014 to 2017. The analysis covers five years and explores which internal characteristics determine organizations’ high disclosure levels in their report. The investigation is conducted through the fuzzy-set Qualitative Comparative Analysis and outlines several different combinations of solutions for the outcome to occur. The study presents a new perspective in the literature as it investigates a niche of organizations largerly unadressed by the literature and adopts a methodology dragged from other fields (e.g., marketing). The results demonstrate different circumstances under which the analyzed condition co-exist and led to high disclosure levels without excluding other conditions.